Individualized task difficulty promotes balance training outcomes and self-efficacy in individuals with lower limb loss. - Wu, Fu-Lien; Chung, Yu-Chen; Lee, Szu-Ping (Prosthetics & Orthotics International, 2026)
An ideal motor skill learning typically features adaptive task difficulty to facilitate training outcomes and avoid frustration, yet this concept has not been explored in balance training for individuals with diminished postural control including lower limb loss. The purposes of this study were (1) to examine a novel stabilometer-based task with individualized difficulty levels as a balance training protocol and (2) to compare the task performance and self-efficacy between participants receiving the training with and without individualized task difficulty. Ten older adults and 10 individuals with unilateral lower limb amputation were recruited. The experimental group received training with task difficulty individualized based on their pretraining weight-bearing capacities, whereas the control group received standard training without difficulty adjustment. Participants were instructed to maintain the stabilometer in a horizontal position for as long as possible over 20 trials (4 blocks, 30 s per trial). Performance feedback and task-related self-efficacy were assessed after each block. Participants in the 2 groups were comparable in age (62.1 vs. 63.5 years), gender composition (4 females), and amputation levels (3 with transfemoral amputation). Significant interactions between group and trial/block in time in balance (experimental group: 7.8 to 16.9 s, control: 8.5 to 8.2 s, P = 0.002), root-mean-square error (experimental group: 10.9° to 6.8°, control: 10.9° to 10.8°, P = 0.002), and self-efficacy (P = 0.005∼0.012) were detected. The training protocol with individualized difficulty levels promoted greater improvements in balance performance and self-efficacy. Individualizing task difficulty based on participant's capacity is important for improving balance performance and self-efficacy. This training protocol is feasible and can be applied clinically to improve balance and postural confidence in individuals with lower limb loss.